Colorless tsukuru tazaki and his years of pilgrimage ebook A novel. - Murakami, Haruki (2014)
INSTANT #1 NEW YORK TIMES BESTSELLER • One of the most revered voices in literature today gives us a story of love, friendship, and heartbreak for the ages. “Mesmerizing, immersive, hallucinogenic.”— Entertainment Weekly Colorless Tsukuru Tazaki and His Years of Pilgrimage is the remarkable story of a young man haunted by a great loss; of dreams and nightmares that have unintended consequences for the world around us; and of a journey into the past that is necessary to mend the present. ONE OF THE BEST BOOKS OF THE YEAR: The New York Times Book Review, The Washington Post, Financial Times, St. Louis Post-Dispatch, Slate, Mother Jones, The Daily Beast, BookPage